Los seres míticos como manifestación cultural - Blache, Marta (Revista Chilena de Humanidades, 2016)
The author examines the cultural condition of folk mythological beings within the larger context of general culture. In this perspective, information is provided on the genesis and function of this class of beings while considering their impact on a human group. In her article, Dr. Blache then singles out for analysis the people's relations with these mythological beings in order to establish the extent to which folk studies can be legitimatively concerned with them.